Taking Advantage of Plant Defense Mechanisms to Promote Human Health. Exploitation of Plant Natural Products for Preventing or Treating Human Disease: Second of Two Parts - Magrone, Thea; Magrone, Manrico; Russo, Matteo A.; Jirillo, Emilio (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: Plants have been regarded as essential source of food for human beings, as confirmed by archeological studies that have revealed the presence of proteins from cereals and legumes on old pottery. Specific Aims: In this review, major health effects derived from the consumption of plant fibers, polyunsaturated fatty acids (PUFAs) and polyphenols, respectively, will be described with special emphasis on their mechanisms of action, both at cellular and molecular levels. Dietary Compounds: Fibers exhibit a prevalent prebiotic effect, acting on the intestinal microbiota with the production of protective metabolites, such as short chain fatty acids. Plant PUFAs include α-linolenic and stearidonic acids, which are the precursors of other two major PUFAs, namely, eicosapentaenoic and docosahexaenoic acids. Some clinical trials demonstrated the ability of PUFAs to lower the risk of coronary disease, while other trials did not confirm such a finding. Polyphenols are endowed with anti-oxidant and anti-inflammatory activity in view of their property to inhibit NF-ΚB activation, to induce the anti-inflammatory T regulatory cells and to normalize the intestinal microbiota. The beneficial effects of polyphenols on obesity/diabetes, allergic/autoimmune and inflammatory disease are elucidated. Conclusion: Plants are one of the major sources of healthy dietary products, whose exploitation may promote prevention of chronic disease.
Keywords: Cellular and molecular rehabilitation